PENERAPAN MEDIA BONEKA TANGAN DALAM PEMBELAJARAN MENGONVERSI TEKS LAPORAN HASIL OBSERVASI MENJADI TEKS DIALOG PADA SISWA SEKOLAH MENENGAH ATAS: Media Puppets Hand, Speech - Ardhianti, Mimas (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2015)
This study aimed to describe the implementation and results of the application of Hand Puppet media in speech class X Ak-2 SMK Antartika 2 Sidoarjo. Media Hand Puppet is a puppet hand puppet media is driven by a person with the way the rest of his fingers put under clothes doll is used as a learning medium education for children who are used to deliver the message in the storytelling. Research using qualitative descriptive technique. Data were taken for this study is based on the observation sheet and questionnaire. While the source of the data taken at 42 Grade X Ak-2 SMK Antartika 2 Sidoarjo. From the observation and questionnaires can be seen that the results of learning by applying Hand Puppets media can assist students in learning Indonesian. There is 97.6% of students whose value meets the minimum passing standard. Meanwhile, 2.3% of students value does not meet the minimum passing standard for their speaking ability is still lacking. The students become more actively talking with the media application Hand Puppet.